2021
DOI: 10.1177/0300060520986708
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of angiopoietin-2 for predicting organ failure in patients with acute pancreatitis: a systematic review and meta-analysis

Abstract: Objective Our aim was to assess the accuracy of angiopoietin-2 (Ang-2) as a prognostic marker for acute pancreatitis (AP) with organ failure (OF). Methods We undertook a systematic search of the PubMed, Cochrane Library, Embase, Chinese Journals Full-text, Wanfang, China Biology Medicine disc, and Weipu databases to identify eligible cohort studies on the predictive value of Ang-2 for AP with OF. The main outcome measures were sensitivity and specificity. The effects were pooled using a bivariate mixed-effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(106 reference statements)
0
2
0
1
Order By: Relevance
“…Further subgroup and sensitivity analyses indicated that Ang-2's most effective predictive ability is observed between 24 and 72 hours after the onset of AP. These findings suggest that Ang-2 has the poten-tial to serve as a valuable predictor of AP severity in future clinical applications (24).…”
Section: Angiopoietin-like Proteinmentioning
confidence: 81%
“…Further subgroup and sensitivity analyses indicated that Ang-2's most effective predictive ability is observed between 24 and 72 hours after the onset of AP. These findings suggest that Ang-2 has the poten-tial to serve as a valuable predictor of AP severity in future clinical applications (24).…”
Section: Angiopoietin-like Proteinmentioning
confidence: 81%
“…Lv Yongcai et al [16] showed that on day 1, Ang-2 predicted POF value better than traditional predictors, with a sensitivity of 83.30%, a specificity of 68.40%, and an AUC of 0.738 when its cut-off value was 126.44 μg/L, whereas Ang-2 predicted PN value as the best single biochemical indicator when the cut-off value of Ang-2 was 130.9 μg/L, it had a sensitivity of 77.3%, a specificity of 73.6%, and an AUC of 0.703. According to a systematic evaluation and meta-analysis by Lv et al [17] the results of a systematic evaluation and meta-analysis showed that Ang-2 had high diagnostic accuracy for AP combined with OF; the sensitivity, specificity, positive likelihood ratio, and negative likelihood ratio of combined OF were 0.93, 0.85, 6.40, and 0.08, respectively. the AUC = 0.95, and the optimal prediction time of Ang-2 might be 24 -72 h after the onset of AP.…”
Section: Angiopoietin 2 (Ang-2)mentioning
confidence: 99%
“…Ангіопоетин-2 -глікопротеїн, що вибірково діє на ендотеліальні клітини та бере участь в ангіогенезі, диференціації клітин та регуляції проникності судинної стінки. Нині існує багато досліджень, присвячених вивченню вмісту ангіопоетину-2 як можливого предиктора розвитку ПОН та тяжкого перебігу ГП (значення, що перевищує 11,76 нг/мл у перші 24 год з моменту появи болю), чутливість тесту становить 100%, специфічність -95,2% [67].…”
Section: прогнозування та оцінка ступеня тяжкості гпunclassified